Effect of fault distribution on hydraulic fracturing: Insights from the laboratory. (January 2021) - Shan, Kun; Zhang, Yanjun; Zheng, Yanhao; Cheng, Yuxiang; Yang, Yunxing
Abstract: In geothermal development, induced earthquakes can be problematic side effects. To research the effect of fault distribution on induced earthquakes by hydraulic fracturing, a series of hydraulic fracturing tests were carried out on granite samples. We compared the performance of intact rock and prefabricated fault rock in the process of hydraulic fracturing, and an acoustic emission (AE) system was used to monitor acoustic emission events in the fracturing process. The test results revealed that fracture pressure increases with the increase of injection rate, and the acoustic emission cumulative energy of the prefabricated fault rock sample was higher than that of the intact rock sample. Also, in the process of fracturing, shear fracture accounted for more than 70% of all fractures for the prefabricated fault rock sample. However, for the intact rock sample, shear fracture only accounted for about 50% of all fractures. Our results support the conclusion that the existence of prefabricated faults could lead to an increase in shear fractures and fracture energy. Highlights: Hydraulic fracturing experiment with intact granite and granite with fault were conducted. The acoustic emission system was used to record the acoustic emission events. The fracture modes and energy were analyzed by acoustic emission parameters. The existence of prefabricated faults could lead to an increase in shear fracture and fracture energy. Shear fracture with higher energy is significantly enhanced in prefabricated fault rocks.